Penerapan Integral Lipat Dua untuk Menghitung Volume Tiang Beton Berbentuk Tabung sebagai Dasar Estimasi Kebutuhan Material pada Struktur Pondasi Gedung - Alvi Sahrin Nasution; Dear Sevtia Br Karo Karo; Gracia Lovian Girsang; Herdita Br. Ginting; Klara Manila Laoli; Windi Suryani (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study examines the application of double integrals in calculating the volume of cylindrical concrete piles as a basis for estimating material requirements in building foundation structures. The volume calculation was carried out using a double-integral approach in polar coordinates for three pile segments with lengths of 4 m, 3.9 m, and 4 m, each having a diameter of 60 cm. The results were then validated using the standard geometric formula to ensure consistency and mathematical reliability. The obtained concrete volume was subsequently used to estimate material needs based on a 1:1.5:3 mix proportion consisting of cement, sand, and gravel. The findings indicate that double integrals can be effectively applied to generate accurate estimations of both volume and material requirements, supporting logistical planning in construction. This approach also highlights the strong connection between mathematical concepts—particularly multivariable calculus—and practical applications in civil engineering. Furthermore, the study emphasizes that double integrals may serve as a relevant alternative when structural modeling requires deeper analytical exploration or validation beyond conventional geometry. Therefore, the implementation of double integrals not only reinforces theoretical understanding but also enhances precision in evaluating structural components within building foundation planning.